2017
DOI: 10.1103/physrevb.96.184105
|View full text |Cite
|
Sign up to set email alerts
|

Force-matched empirical potential for martensitic transitions and plastic deformation in Ti-Nb alloys

Abstract: A force-matched spline-based empirical potential based on the modified embedded-atom method is fit to an extensive database of highly-converged density functional theory calculations for titaniumniobium alloys with an evolutionary algorithm. Consistency with experiment and existing models is verified through calculations of structural, elastic and thermal properties. The potential is used to study the effects of alloying on elastic properties, the martensite phase of Ti-rich alloys and the α-β and β-ω transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Therefore we highlight that all the calculated properties must be derived from reasonable simulated configurations in the current conditions, which in turn are powerful indicators that will 'spontaneously' select suitable potential forms and parameters, obeying the basic logic that FF modeling is actually the inverse problem of the corresponding simulation. This is essential for all FF study involving potential development [136,137] and modification [138][139][140][141][142].…”
Section: Potential Assessmentmentioning
confidence: 99%
“…Therefore we highlight that all the calculated properties must be derived from reasonable simulated configurations in the current conditions, which in turn are powerful indicators that will 'spontaneously' select suitable potential forms and parameters, obeying the basic logic that FF modeling is actually the inverse problem of the corresponding simulation. This is essential for all FF study involving potential development [136,137] and modification [138][139][140][141][142].…”
Section: Potential Assessmentmentioning
confidence: 99%
“…To further substantiate the presence of the interfacial ω-phase, additional analysis was conducted on the grain boundary orientations, as depicted in Figure 6. Substructures c and d in Figure 6a correspond to those in Figures 6c and 6d Lai et al [48] and Ehemann et al [51] also calculated the energy change from the phase to the ω-phase of Ti-Nb alloys. They determined that the ω-phase structure p sesses lower energy compared to the β-phase.…”
Section: ω-Phase Transformationmentioning
confidence: 71%
“…The details of the hexagonal transformation path can be found in Refs. 50, 90, and 91; the bcc → ω transition consists of a shuffling of pairs of atoms along the [111] direction of bcc, corresponding to the 2 3 [111] phonon 23 . For simplicity, the volume of the unit cell was taken as constant along the transformations.…”
Section: Properties Of Bulk Phasesmentioning
confidence: 99%
“…For instance, it has been reported that an accurate description of the ω phase [14][15][16][17][18][19] or of the temperature-dependent behavior of the bcc phase [20,21] needs to be sacrificed to achieve an overall good accuracy of the potential. A few potentials have succeeded to reproduce at least the α, β, and ω phases quantitatively [22][23][24] by increasing the model complexity and by employing non-smooth interpolators, which however might lead to overfitting. The transferability of these more complex potentials to properties or environments not included in the training has been questioned [18,25].…”
Section: Modelling and Simulation In Materials Science And Engineeringmentioning
confidence: 99%
See 1 more Smart Citation